Private policing - Button, Mark. (Cullompton, Devon, UK ; Portland, Or. : Willan Pub., 2002)
Private Policing examines the origins of private policing, the growi ng literature that has sought to explain its growth, and ways in which it has been defined and classified.
Includes bibliographical references (p. 135-148) and index.
Keywords: Police, Private